Diversidade, especificidade e estrutura genética populacional de parasitos diplostomídeos em peixes dulcícolas neotropicais. - Souza, Geza Thais Rangel e (2014)
Diplostomoidea species are related as cosmopolitan, however their real diversity and specificity may be covered by identification mistakes. The CO1 gene was used to identify the parasite species, aiming to analyze the diversity of the diplostomoid found on the fish`s eyes and to examine the population local adaptation of Austrodiplistomum ostrowskiae on South America. It was tested the host specificity hypothesis, predicting that most of the species observed would present a strong specific distribution to the fish host and to the micro-habitat explored was tested. Six species were molecularly characterized and they demonstrated specificity to the host, to the explored resource or to both of them. The parasite distribution among the studied hosts demonstrated a niche partition between the specialist species on the vitreous humor resources, not occurring co-occurring on the same niche. It was concluded that the metacercariae are specific to the explored resource, that there are cryptic species on the area and that ecological factors may direct the host switch in some parasite groups. A parasite species widely distributed on fishes from South America was used to test the local adaptation hypothesis, analyzing the existence of the parasite gene flux between different hosts of these areas. The population genetic structure of A. ostrowskiae was evaluated, on regional and continental scale, by a Molecular Variance Analysis (AMOVA). There was not a genetic structure, especially due to the allogenic life cycle particularities and to the migration of the definitive hosts. The host-parasite interactions appear to be recent (with low evolutionary time), which can be demonstrated by high haplotype diversity and low nucleotide diversity, distributed among subpopulations. The parasites subpopulations sampled on the studied hydrographic basins correspond to a single metapopulation, of continental distribution.